EFEKTIVITAS PELAKSANAAN PROGRAM PENDIDIKAN KHUSUS OLEH DINAS PENDIDIKAN PROVINSI RIAU TAHUN 2018 (Studi Kajian Sekolah Luar Biasa Negeri Siak) - Rachma Della Frizliana Amanda; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The need for education is a right for every citizen, without the exception of the right for children with disabilities or special needs. The Indonesian government operates and has a special school to accommodate children with special needs (diffable). The special school is known as the Special School (SLB). Special Schools (SLB) become a means or forum for developing the abilities of children with special needs by providing guidance to Special Schools (SLB) which includes students and their educators. This of course must get special attention from the government.The purpose of this study was to determine the effectiveness of the implementation of special education programs by the Riau Provincial Education Office in 2018. The location of this research was carried out at the Riau Provincial Education Office and Siak State Special School. This study uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.The result of this research is that the Special Education Program by the Riau Provincial Education Office in 2018 cannot be said to be effective. This can be seen from the accuracy of program targets at the Siak State School which have not been achieved and have not met the target. Then the socialization of the program that has been carried out directly by the Riau Provincial Education Office through a coordination meeting with the heads of special schools, however, not all activities are carried out first. Achieving program objectives that have not been achieved due to the development of special schools in Riau Province, especially the Siak State Special School, have not fully achieved the goals. In addition, monitoring is also not effective because it is only carried out at the beginning of the activity by the Riau Provincial Education Office but is not carried out again when the activity is already running. And those that affect the effectiveness of the implementation of this special education program are the quality of the apparatus, the competence of administrators, infrastructure, and also supervision.Keywords : Accuracy of Program Targets, Program Socialization, Program Objectives, Program Monitoring.